Unraveling the assembloid: Real-time monitoring of dopaminergic neurites in an inter-organoid pathway connecting midbrain and striatal regions - Alp Ozgun; David J. Lomboni; Amy Aylsworth; Allison Macdonald; William A. Staines; Marzia Martina; Michael G. Schlossmacher; Joseph S. Tauskela; John Woulfe; Fabio Variola (Materials Today Bio, 2024)
Modern in vitro technologies for preclinical research, including organ-on-a-chip, organoids- and assembloid-based systems, have rapidly emerged as pivotal tools for elucidating disease mechanisms and assessing the efficacy of putative therapeutics. In this context, advanced in vitro models of Parkinson's Disease (PD) offer the potential to accelerate drug discovery by enabling effective platforms that recapitulate both physiological and pathological attributes of the in vivo environment. Although these systems often aim at replicating the PD-associated loss of dopaminergic (DA) neurons, only a few have modelled the degradation of dopaminergic pathways as a way to mimic the disruption of downstream regulation mechanisms that define the characteristic motor symptoms of the disease. To this end, assembloids have been successfully employed to recapitulate neuronal pathways between distinct brain regions. However, the investigation and characterization of these connections through neural tracing and electrophysiological analysis remain a technically challenging and time-consuming process. Here, we present a novel bioengineered platform consisting of surface-grown midbrain and striatal organoids at opposite sides of a self-assembled DA pathway. In particular, dopaminergic neurons and striatal GABAergic neurons spontaneously form DA connections across a microelectrode array (MEA), specifically integrated for the real-time monitoring of electrophysiological development and stimuli response. Calcium imaging data showed spiking synchronicity of the two organoids forming the inter-organoid pathways (IOPs) demonstrating that they are functionally connected. MEA recordings confirm a more robust response to the DA neurotoxin 6-OHDA compared to midbrain organoids alone, thereby validating the potential of this technology to generate highly tractable, easily extractable real-time functional readouts to investigate the dysfunctional dopaminergic network of PD patients.